2016
DOI: 10.1016/j.ejvs.2015.09.025
|View full text |Cite
|
Sign up to set email alerts
|

Design of a New Risk Score in Critical Limb Ischaemia: The ERICVA Model

Abstract: The ERICVA model has a good predictive capacity for death and/or major amputation in the clinical setting, and is better than the PREVENT III and Finnvasc scores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 14 publications
1
16
0
Order By: Relevance
“…[13,14,15,21,22,23,24,25] Findings of the present study are consistent with several of these previous studies that also identified that WBC, PLR levels, and RC at hospital admission were important risk factors for LEA. [10,13,14]…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…[13,14,15,21,22,23,24,25] Findings of the present study are consistent with several of these previous studies that also identified that WBC, PLR levels, and RC at hospital admission were important risk factors for LEA. [10,13,14]…”
Section: Discussionsupporting
confidence: 91%
“…[9,10,11,13,14,15,16,20,21,22,23,24,25,26,27] Results of studies designed to assess the risk of LEA in CLI patients following bypass surgery have also been reported previously. [13,14,15,21,22,23,24,25] Findings of the present study are consistent with several of these previous studies that also identified that WBC, PLR levels, and RC at hospital admission were important risk factors for LEA. [10,13,14]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Established factors associated with increased 2-year mortality in CLI patients include age, body mass index (BMI), nonambulatory status, hemodialysis, cerebrovascular disease, left ventricular ejection fraction <40%, and tissue loss. 4 Several studies have attempted to generate risk assessment models to aid in clinical decision making for management of patients with CLI, 5,6 but none of these models currently incorporates angiographic information. While it has been suggested that distal PAD is associated with unique characteristics and worse survival outcomes compared to proximal disease, even after controlling for typical risk factors, 7 the impact of lesion location and extent on outcomes in CLI remains uncertain.…”
Section: Introductionmentioning
confidence: 99%